Circularly Polarized Hexagonal Microstrip Antenna Loaded with Slot and Complementary Split Ring Resonator - Sadiq Ahmed; Amer Abbood Albehadili; Zahraa H. Mohammed; Zaid A. Abdul Hassain; Mohammed Al-Saadi; Madhukar Chandra (Journal of Engineering and Sustainable Development, 2024)
The development of a compact and straightforward circularly polarized hexagon-microstrip patch antenna with two layers and a single feed is presented. Circular polarization is achieved using two strategies. The first technique incorporates a narrow slot along one vertex of a hexagonal patch's diagonal, opposite the feed line. The second one is based on embedding a complementary split ring resonator on the hexagonal patch. The proposed antenna is excited by an aperture coupling feed, and it is implemented on two substrate materials; the patch substrate is Roger droid/RT-5880, and the second feed substrate is RO 4350. This work compares the performance of the suggested antennas, including their radiation characteristics, axial ratio, and return loss, in two different scenarios. The proposed antenna has overall dimensions of (0.8λ0 - 0.8λ0 - 0.037λ0) at 3.4 GHz. The slot patch antenna has 2.65% bandwidth for its 3-dB axial ratio and 5.71% impedance bandwidth from 3.4 to 3.6 GHz at 3.5 GHz of the center frequency. The proposed patch antenna also demonstrates a maximum gain of 1.2 dBi. High-frequency structure simulation software was used to design and simulate the proposed hexagon configurations.